2014
DOI: 10.35818/acta.v8i2.124
|View full text |Cite
|
Sign up to set email alerts
|

Características Da Carcaça De Bovinos Sindi E Bubalinos Mediterrâneos Em Confinamento

Abstract: Objetivou-se com esta pesquisa avaliar as características da carcaça de bovinos Sindi e bubalinos Mediterrâneos abatidos com pesos médios semelhantes. O experimento foi realizado na UFRuralRJ, onde 14 animais inteiros foram terminados em confinamento (7 bovinos e 7 bubalinos), recebendo a mesma dieta no período de dezembro de 2004 a abril de 2005. Os animais foram abatidos quando alcançaram pesos médios de 488,3 ± 8,94 kg para bovinos Sindi e 492,5 ± 8,61 kg para bubalinos Mediterrâneos. O delineamento experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
0
1
1
Order By: Relevance
“…In addition, buffalo slaughtered with higher body weights have higher hot and cold carcass yields (Rashad et al, 2019). The averages obtained in this study for carcass yields were lower than that observed by Cabral Neto et al (2013), which were 48.3 and 47% for hot and cold carcass yields, respectively, for Mediterranean buffalo in a feedlot.…”
Section: Resultscontrasting
confidence: 61%
“…In addition, buffalo slaughtered with higher body weights have higher hot and cold carcass yields (Rashad et al, 2019). The averages obtained in this study for carcass yields were lower than that observed by Cabral Neto et al (2013), which were 48.3 and 47% for hot and cold carcass yields, respectively, for Mediterranean buffalo in a feedlot.…”
Section: Resultscontrasting
confidence: 61%
“…A carne bubalina, é comercializada e identificada como bovina, o que impede a agregação de valor ao produto, pois a população não tem a liberdade de escolha, e nem conhece as vantagens de consumir a carne oriunda dos búfalos (Jorge et al, 1997. Jorge, 1999Cabral Neto, 2013).…”
Section: Produção De Carneunclassified